도시가구의 시설과실 구매실태와 시사점 - 김경필 (한국농촌경제연구원, 2005)
ABSTRACT There are two main purposes of this study. One is to grasp substitute items for the fruits cultivated in greenhouse. The other is to grasp the consumer's preference and present its implication for fruit production in Korea. The items studied include grapes and tangerines. For the study method, a consumer survey for urban households was conducted. The survey result reveals that greenhouse-cultivated grape tends to be substituted with watermelon, peach, and tomato. And the substitute items of greenhouse-cultivated tangerine are orange, watermelon, peach, and tomato. The consumer's satisfaction in the quality of greenhouse-cultivated fruits is generally high.
Keywords: 하우스포도; 하우스온주감귤; 대체과일; 구매실태; greenhouse-grape; greenhouse-tangerine; substitute fruit; consumer behavior